Liquid exfoliated Co(OH)2 nanosheets as low-cost, yet high-performance, catalysts for the oxygen evolution reaction - McAteer, David; Godwin, Ian J.; Ling, Zheng; Harvey, Andrew; He, Lily; Boland, Conor S.; Vega‐Mayoral, Victor; Szydłowska, Beata; Rovetta, Aurélie A.; Backes, Claudia; Boland, John B.; Chen, Xin; et al. (Advanced energy materials, 2018)
Identifying cheap, yet effective, oxygen evolution catalysts is critical to the advancement of water splitting. Using liquid exfoliated Co(OH)2 nanosheets as a model system, a simple procedure is developed to maximize the activity of any oxygen evolution reaction nanocatalyst. First the nanosheet edges are confirmed as the active areas by analyzing the catalytic activity as a function of nanosheet size. This allows the authors to select the smallest nanosheets (length ≈50 nm) as the best performing catalysts. While the number of active sites per unit electrode area can be increased via the electrode thickness, this is found to be impossible beyond ≈10 µm due to mechanical instabilities. However, adding carbon nanotubes increases both toughness and conductivity significantly. These enhancements mean that composite electrodes consisting of small Co(OH)2 nanosheets and 10 wt% nanotubes can be made into freestanding films with thickness of up to 120 µm with no apparent electrical limitations. The presence of diffusion limitations results in an optimum electrode thickness of 70 µm, yielding a current density of 50 mA cm−2 at an overpotential of 235 mV, close to the state of the art in the field. Applying this procedure to a high-performance catalyst such as NiFeOx should significantly surpass the state of the art.
Im Titel ist die Zahl "2" tiefer gestellt
Gesehen am 24.03.2020